Results on ϕ-like functions involving Hadamard product - KAUR, Hardeep; BRAR, Richa; BILLING, Sukhwinder Singh (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
In this paper, we derive a differential subordination theorem involving convolution of normalized analytic functions. By selecting different dominants to our main result, we find certain sufficient conditions for ϕ−likeness and parabolic ϕ−likeness of functions in class A. Mathematics Subject Classification (2010): 30C80; 30C45. Received 25 February 2025; Accepted 31 May 2025